SPE International Symposium on Oilfield Chemistry 2011
DOI: 10.2118/141462-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Alteration and Foam Mobility Control in a Layered 2-D Heterogeneous System

Abstract: In a layered 2-D heterogeneous sandpack with 19:1 permeability contrast that was preferentially oil-wet, the recovery by waterflood was only 49.1% of original oil-in-place (OOIP) due to injected water flowing through high-permeability zone leaving low-permeability zone unswept. In order to enhance oil recovery, an anionic surfactant blend (NI) was injected that altered the wettability and lowered the interfacial tension (IFT) and consequently enabled gravity and capillary pressure driven vertical counter-curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Their results showed a direct correlation between the critical capillary pressure and the final height of foam. It has been observed that mixing surfactants can significantly improve the stability of foams and potentially reduce the destabilizing effect of oil on foam [28,42]. For example addition of small fractions of non-ionic surfactant to an anionic surfactant enhances the foam stability as a result of the formation of a viscous surface layer which raises the interfacial viscosity of the foam thereby reducing the rate of film thinning [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed a direct correlation between the critical capillary pressure and the final height of foam. It has been observed that mixing surfactants can significantly improve the stability of foams and potentially reduce the destabilizing effect of oil on foam [28,42]. For example addition of small fractions of non-ionic surfactant to an anionic surfactant enhances the foam stability as a result of the formation of a viscous surface layer which raises the interfacial viscosity of the foam thereby reducing the rate of film thinning [19].…”
Section: Introductionmentioning
confidence: 99%
“…Betaines are known for their foam enhancing properties [14]. In their 2D sand-pack experiments, Li et al [42] observed that the addition of lauryl betaine to the so called NI blend (4:1 of Neodol 67-7PO sulfate and IOS 15-18) generated a stronger and more stable foam in the presence of oil. One of the mechanisms suggested for this stabilising behavior is that betaine increases the critical capillary pressure required for droplet entry which is related to the disjoining pressure [14,43].…”
Section: Introductionmentioning
confidence: 99%
“…Foam is a proven gas mobility control method in fields (Blaker et al, 2002, Enick and Olsen, 2012 and in numerous studies (Bernard and Holm, 1964, Holm, 1968, Rossen, 1996, Schramm, 1994, Llave et al, 1990, Lawson and Reisberg, 1980. More recently, foam has been suggested as a gas diversion agent in stratified systems (Bertin et al, 1999, Tanzil et al, 2002, Nguyen et al, 2003, Siddiqui et al, 2003, Li et al, 2010, Li et al, 2011, Conn et al, 2014 and in fractures and fracture networks (Kovscek et al, 1995, Yan et al, 2006, Fjelde et al, 2008, Buchgraber et al, 2012b, Haugen et al, 2012. Nguyen et al (2003) demonstrated gas diversion in a layered system, and found that foam penetration depth in the low permeable layer increased when capillary cross-flow was allowed, even if the layers were parallel to the main flow direction.…”
Section: Foam Injectionmentioning
confidence: 99%
“…In contrast, the NI blend (4:1 blend of Neodol 67-7PO sulfate and internal olefin sulfonate (IOS 15-18)) does not generate a strong foam. However, mixing lauryl betaine (LB) with the NI blend can generate foam that is even more stable than the one generated by AOS itself . Thus, lauryl betaine, a foam booster, can help stabilize foam even in the presence of oil .…”
Section: Introductionmentioning
confidence: 99%